Please call me John: name choice and the assimilation of immigrants in the United States, 1900–1930 - Carneiro, Pedro (2021)
The majority of immigrants to the United States at the beginning of the 20th century adopted American first names. In this paper we study the economic determinants of name choice, by relating the propensity of immigrants to carry an American first name to the local concentration of their compatriots and local labor market conditions. We find that high concentrations of immigrants of a given nationality discouraged members of that nationality from taking American names, in particular for more recent arrivals. In contrast, labor market conditions for immigrants do not seem to be associated with more frequent name changes among immigrants.